2016
DOI: 10.2967/jnumed.115.171231
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Acquisition Time Window and Simplified Quantification of Dopamine Transporter Availability Using 18F-FE-PE2I in Healthy Controls and Parkinson Disease Patients

Abstract: nortropane ( 18 F-FE-PE2I) is a newly developed dopamine transporter (DAT) PET radioligand. Full quantification methods rely on dynamic acquisition of 18 F-FE-PE2I, but in a clinical setting a simplified protocol is preferable. The aims of this study were to identify the optimal acquisition time window for 18 F-FE-PE2I and to validate the specific binding ratio (SBR) as a simplified quantification method. Methods: Ten Parkinson disease (PD) patients and 10 controls were included. Ninety-three-min dynamic PET m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…The first study, including 10 Parkinson disease patients and 10 age-and sex-matched control subjects, demonstrated the ability of 18 F-FE-PE2I to quantify the nigrostriatal DAT loss in Parkinson disease (9). Findings from further studies supported the use of 18 F-FE-PE2I as a diagnostic tool for the evaluation of parkinsonian patients in the clinical setting (9)(10)(11).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…The first study, including 10 Parkinson disease patients and 10 age-and sex-matched control subjects, demonstrated the ability of 18 F-FE-PE2I to quantify the nigrostriatal DAT loss in Parkinson disease (9). Findings from further studies supported the use of 18 F-FE-PE2I as a diagnostic tool for the evaluation of parkinsonian patients in the clinical setting (9)(10)(11).…”
mentioning
confidence: 84%
“…18 F-(E)-N-(3-iodoprop-2-enyl)-2b-carbofluoroethoxy-3b-(49methyl-phenyl) nortropane ( 18 F-FE-PE2I) is a recently developed radioligand that shows suitable characteristics for a DAT imaging tool both in nonhuman primates (NHPs) and in human subjects. The fast washout from the brain and the favorable metabolism make 18 F-FE-PE2I superior to other related PET radioligands (e.g., 11 C-PE2I and 18 F-FECNT) for DAT quantification (5)(6)(7). In addition, the relatively high specific-to-nondisplaceable binding ratio of 18 F-FE-PE2I permits quantification of the DAT also in extrastriatal regions, such as the substantia nigra, where the cell bodies of the dopaminergic neurons are located.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presynaptic dopamine transporter (DAT) can be targeted with compounds such as 18 F-FP-CIT, 11 C-methylphenidate ( 11 C-MP) or 18 F-FE-PE2I (Sonni et al, 2016). The intracellular vesicular monoamine transporter (VMAT2) is responsible for re-packaging dopamine into vesicles, and is commonly labelled with 11 C-dihydrotetrabenazine ( 11 C-DTBZ) or 18 F-fluoropropyl-dihydrotetrabenazine ( 18 F-FP-DTBZ).…”
Section: Neuroimaging In Pre-motor Parkinson'smentioning
confidence: 99%
“…[ 18 F]FE-PE2I, developed in 2009 [1,2], has, through several validity studies, proven to be a valuable positron emission tomography (PET) radioligand for dopamine transporter (DAT) imaging [1][2][3][4][5][6][7][8]. A clinical PET study with [ 18 F]FE-PE2I in 20 patients with early-stage PD showed an in vivo striato-nigral gradient of DATloss [9], in agreement with post-mortem studies in patients, and animal model studies [10,11].…”
Section: Introductionmentioning
confidence: 54%